Ensaio, ciência e história em Os parceiros do Rio Bonito: uma leitura historiográfica da obra de Antonio Candido - Hugo Mateus Goncalves Rocha (2017)
In this research, we analyze the book, ¯Os Parceiros do Rio Bonito: estudo do caipira paulista e a transformação dos seus meios de vida by the sociologist and literary critic Antonio Candido de Mello e Souza. In this way, we seek to explore the dialogues established by the author with brazilian social thought produced between the 1900s and 1950s. The central idea behind research is to explore how by specifically analyzing a process of on going social transformation in culture, the author used a different material, which included theoretical and methodological axes of Sociology and Anthropology, along with historiographical interpretations of bandeirante expansion, as well as references to brazilian social thought from the decades of 1900 to 1940, recognized as part of the essayistic tradition in national thought. Thus, in the first chapter, we seek to explore the authors options in developing his research and dividing it into three sections. In the second chapter, we try to understand how the author established the central guidelines for the identification of the caipira and its societies. Finally, in the third chapter, we tried to justify that in endeavoring to carry out that study, Antonio Candido would have developed a text that, although generated from an academic research, ¯Os Parceiros do Rio Bonito can also be interpreted as a work which presents elements of both the tradition of Brazilian thought in the early twentieth century and the sociological research model that took shape in Brazil from the mid - 1940s and 1950s.